Assessing the causal effects of Eubacterium and Rumphococcus on constipation: a Mendelian randomized study - Zhang, Xiao; Chen, Jiang; He, Feng; Du, Wenchun; Yu, Xianhao (Frontiers in Microbiology, 2024)
Background: Constipation is affected by a number of risk variables, including cardiovascular disease and growth factors. However, the impacts of gut flora on constipation incidence has not been shown. This work, Single-Variable Mendelian Randomization (SVMR) was utilized to estimate the causal relationship between the Eubacterium genus or Rumphococcus, and constipation.: Data for constipation, Eubacterium genus and Rumphococcus were taken from the Integrated Epidemiology Unit (IEU) open GWAS database. Including 218,792 constipation samples, and there were 16,380,466 Single Nucleotide Polymorphisms (SNPs) for constipation. The ids of Eubacterium genus and Rumphococcus were sourced from MiBioGen database. The sample count for the Eubacterium genus was 17,380, with 656SNPs. In addition, the sample size for Rumphococcus was 15,339, with 545 SNPs. The SVMR was performed to assess the risk of Eubacterium genus and Rumphococcus in constipation using weighted median, MR Egger, simple mode, inverse variance weighted (IVW), and weighted mode. Finally, we did a sensitivity analysis that included a heterogeneity, horizontal pleiotropy, and Leave-One-Out (LOO) test to examine the viability of the MR data.The SVMR revealed that the Eubacterium genus and Rumphococcus were causally connected to constipation, with Rumphococcus (P = 0.042, OR = 1.074) as a hazardous factor and Eubacterium genus (P = 0.004, OR = 0.909) as a safety factor.Sensitivity tests then revealed the absence of variability between the constipation and the exposure factors (Eubacterium genus and Rumphococcus). Additionally, there were no other confounding factors and the examined SNPs could only influence constipation through the aforementioned exposure factors, respectively. As a result, the MR results were fairly robust.Our investigation verified the causal links between the Eubacterium genus or Rumphococcus, and constipation, with greater Rumphococcus expression increasing the likelihood of constipation and the opposite being true for the Eubacterium genus.